Excel statistics : a quick guide - Salkind, Neil J. (SAGE, 2013)
Shows readers how to utilize the features of Microsoft® Excel to answer both simple and complex questions about data analysis. Part I explores thirty-five Excel functions while Part II of the text contains fifteen Analysis Toolpak tools. The description and use of each function and tool appear on one page with corresponding screen shots of the element in action on the facing page, allowing the user to see what each function or tool looks like as it is being applied. The actual data files used in the examples are also available to readers. Excel novices and experts alike will find this text not only practical but also easy to use and engaging.